Axitinib after Sunitinib in Metastatic Renal Cancer: Preliminary Results from Italian “Real-World” SAX Study - D'Aniello, Carmine; Vitale, Maria G.; Farnesi, Azzurra; Calvetti, Lorenzo; Laterza, Maria M.; Cavaliere, Carla; Della Pepa, Chiara; Conteduca, Vincenza; Crispo, Anna; De Vita, Ferdinando; Grillone, Francesco; Ricevuto, Enrico; et al. (Frontiers in Pharmacology, 2016)
Axitinib is an oral angiogenesis inhibitor, currently approved for treatment of metastatic renal cell carcinoma (mRCC) after failure of prior treatment with Sunitinib or cytokine. The present study is an Italian Multi-Institutional Retrospective Analysis that evaluated the outcomes of Axitinib, in second-line treatment of mRCC. The medical records of 62 patients treated with Axitinib, were retrospectively reviewed. The Progression Free Survival (PFS), the Overall Survival (OS), the Objective Response Rate (ORR), the Disease Control Rate (DCR) and the safety profile of axitinib and sunitinib-axitinib sequence, were the primary endpoint. The mPFS was 5.83 months (95% CI 3.93-7.73 months). When patients was stratified by Heng score, mPFS was 5.73, 5.83, 10.03 months according to poor, intermediate and favourable risk group respectively. The mOS from the start of axitinib was 13.3 months (95% CI 8.6-17.9 months); the observed ORR and DCR were 25% and 71%, respectively. When stratified patients by subgroups defined by duration of prior therapy with Sunitinib (≤ vs >median duration), there was a statistically significant difference in mPFS with 8.9 ( 95% CI 4.39-13.40 months) vs 5.46 months (95% CI 4.04-6.88 months) for patients with a median duration of Sunitinib >13.2 months. DCR and ORR to previous Sunitinib treatment was associated with longer statistically mPFS, 7.23 (95% CI 3.95-10.51 mo, p=0.01) and 8.67 (95% CI 4.0-13.33 mo, p=0.008) vs 2.97 (95% CI 0.65-5.27 mo, p=0.01) and 2.97 months (95% CI 0.66-5.28 mo, p=0.01) respectively. Overall Axitinib at standard schedule of 5 mg bid, was well tolerated. The most common adverse events of all grades were fatigue (25.6%), hypertension (22.6%), gastro-intestinal disorders (25.9%) and hypothyroidism (16.1%). The sequence Sunitinib-Axitinib was well tollerated without worsening in side effects, with a median OS of 34.7 months (95% CI 18.4-51.0 months). Our results are consistent with the available literature; this retrospective analysis confirms that Axitinib is effective and safe in routine clinical practice.